Infiltrasi Kisah Israiliyyat Tafsir Era Modern: Studi Kisah Tabut Surah al-Baqarah Ayat 24 - Aminatul Khusnah; Salamah Noorhidayati (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Currently, many modern scholars still quote and quote the history of Isra’iliyyat in their tafsir works, in their tafsir books there is the position of modern interpretive scholars regarding the phenomenon of IIsra’iliyyat in starting from rejection to acceptance of the history of IIsra’iliyyat. This article attempts to conduct a study of the history of Isra’iliyyat contained in Surah al-Baqarah verse 248 and examine the position of modern interpretive scholars regarding the history of Isra’iliyyat. The choice of Surah al-Baqarah verse 248 is because this verse is one of the verses that tells the story of Isra’iliyyat which is popular among the people of Israel, namely about the story of the 'Ark' which is a box-shaped object which is a sacred item for the people of Israel. Israel. This analysis uses several modern era tafsir books that are popular among researchers of Al-Qur'an Tafsir, namely M. Quraish Shihab, Hamka, and Wahbah Az-Zuhayli. The results of the analysis show that several commentators' positions in narrating the story of Isra’iliyyat M. Quraish Shihab and Wahbah Az-Zuhayli tend to regard it as a source and only include the story of Isra’iliyyat. Hamka responded to the history of Isra’iliyyat critically.